From Challenges to Transformation: The Professional Development Journey of Transnational Language Teachers in the United States - Wu, Yu; Gao, Huan (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2025)
In the context of global educational exchange, this study explores the experiences of Chinese teachers temporarily teaching Mandarin Chinese in United States K-12 schools. Using case-study methodology, this research examines the professional challenges and learning experiences of these transnational Chinese language teachers. Findings reveal that teachers’ career difficulties arise from the use of teaching strategies that do not align well with the environments of the host schools and from insufficient cultural sensitivity. Moreover, inadequate pre-service training and limited professional development opportunities exacerbate these challenges, prompting self-directed transformative learning efforts. The findings also emphasize how tailored training combined with teachers' transformative learning initiatives can effectively address and mitigate the difficulties faced in transnational teaching environments. This study provides valuable insights into the preparation for transnational educators navigating cross-cultural teaching landscapes, thereby contributing to the discourse on international teacher-exchange programs.